Financial exclusion as a result of limited financial literacy in the context of the financialization process - Maciejasz-Świątkiewicz, Marta (Wykluczenie finansowe jako skutek ograniczonych umiejętności finansowych w kontekście procesu finansjalizacji, 2015)
Today financial literacy and consciousness seems to be indispensable for the proper participation in the financial services market. In the face of the financialization process, the lack of or even insufficient financial knowledge and consciousness, can lead to serious consequences, including financial exclusion. Financial consciousness can be defined as a phenomenon connected with being aware of financial incidents and processes and having the capability to explore and evaluate these phenomena, or as a complex psychological formation acting to control one’s financial behaviour. Financial literacy is a part of financial consciousness. This article shows how and in what way financial literacy and consciousness are responsible for the financial exclusion diagnosed in the survey. The aim of the article is to answer the question whether the lack of or insufficient financial literacy can be responsible for financial exclusion
Nauki o Finansach = Financial Sciences, 2015, Nr 4 (25), s. 90-101
Keywords: financial exclusion; financial literacy; financial inclusion; financialization; wykluczenie finansowe; włączenie finansowe; finansjalizacja